Rasch Rating Scale Model: Bias Detection and Validation Test of Indonesian-Adolescent Life Satisfaction Scale - Yonathan Natanael; Rahmaditya Salsabilla; Denisa Aulia; Dwi Khoirunnisa; Husna Nursaid Munawar; Nada Salsabila Hidayat; Romi Faizal Firdaus (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2022)
Life satisfaction instrument among psychology related analyses has weaknesses in terms of gender bias testing, especially among adolescents. Therefore, this research aims to develop and validate a life satisfaction instrument in the Indonesian language which is new and undetected by gender bias. The modern construct-oriented scale construction method was selected as a guide in developing the instrument, and the participants were 474 adolescents from various cities in Indonesia. At the initial screening stage using the Rasch model analysis, 54 participants were detected as outliers, hence further analysis was only conducted on 420. The results show that I-ALSS fulfills the assumptions of unidimensional and local independence, with a good reliability score. Furthermore, I-ALSS correctly categorizes answer choices into 8 items, without detecting gender bias. Therefore, it is a fairly good instrument to be used in Indonesia.